PENGARUH KEPEMIMPINAN TRANFORMASIONAL DAN TRANSAKSIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU SMK â€œMâ€ PEKANBAR - Yapentra, Arhipen; Herman, Herman (Eko dan Bisnis: Riau Economic and Business Review, 2020)
The research objective was to analyze the effect of Â tranformational and transactional leadership towards Organizational Citizenship Behavior (OCB) of Teachers of Â SMK "M" Pekanbaru. The population and sample in this study used the census method with 47 respondents. Using descriptive and quantitative research methods and multiple linear regression data analysis techniques. Based on the results of the multiple linear regression test, the partial test results for Transformational Leadership Variables (X1) are obtained, t count> t table (3.041> 2.015). Furthermore, the partial test results for the Transactional Leadership Variable (X2), obtained t count > t table (2,719 > 2,015). Both are variable X with probability <0.05. This means that Transformational Leadership (X1) and Transactional Leadership (X2) partially have a positive and significant effect on OCB at SMK â€œMâ€ Pekanbaru. Likewise, the simultaneous test results obtained the value of F count > Ftable (30.549> 3,210) with a probability of 0.000 <0.05. This means that the variables of Transformational Leadership (X1) and Transactional Leadership (X2)Â  simultaneously have a positive and significant effect on OCB at SMK â€œMâ€ Pekanbaru. The magnitude of the influenceÂ  both of variables on OCB at SMK â€œMâ€ of Pekanbaru, based on the Determination Coefficient Test, obtained 56.2% and the remaining 43.8% is influenced by other variables not included in this study